Co-authorship and Academic Productivity in Economics: Interaction Maps from the Complex Networks Approach - José Alberto Molina; Alberto Alcolea; Alfredo Ferrer; David I\~niguez; Alejandro Rivero; Gonzalo Ruiz; Alfonso Tarancón (Institute for the Study of Labor (IZA), 2016)
We explore the relationship between collaborations in writing papers and the academic productivity of economists and, particularly, we describe the magnitude and intensity of co-authorship among economists. To that end, we employ interaction maps from Complex Systems methods to study the global properties of specific networks. We use 8,253 JCR papers from ISI-WOK, published by 5,188 economists from Spanish institutions, and their co-authors, up to 8,202 researchers, from 2002 to 2014, to identify and determine the collaborative structure of economics research in Spain, with its primary communities and figures of influence. Our results indicate that centrality and productivity are correlated, particularly with respect to a local estimator of centrality (page rank), and we provide certain recommendations, such as promoting interactions among highly productive authors who have few co-authors with other researchers in their environment, or recommending that authors who may be well-positioned but minimally productive strive to improve their productivity.
Keywords: A11; C45; C63; D85; I23; Y91; 330; co-authorship; academic productivity; economists; interaction maps; complex networks